2016
DOI: 10.1177/0363546515617737
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management After Outpatient Anterior Cruciate Ligament Reconstruction

Abstract: These results provide the best available evidence from RCTs on pain control regimens after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 124 publications
2
101
0
Order By: Relevance
“…Opioid use after orthropaedic surgery has been a significant issue [10,12,[13][14][15][16][17]19,21,22]. After ACLR acute pain management is routinely necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opioid use after orthropaedic surgery has been a significant issue [10,12,[13][14][15][16][17]19,21,22]. After ACLR acute pain management is routinely necessary.…”
Section: Discussionmentioning
confidence: 99%
“…We used intra-articular bupivacaine injections, compression cryotherapy and non-steroidal anti-inflammatory medication in the post-operative period. All of which have been shown to decrease opioid consumption after ACLR [15]. A complexity of our study could be in how we identified our three groups based on the amount of medication given or number of weekly prescriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain control is not only essential for early exercise, return to normal life, improvement of respiratory capability, and reduced respiratory complications, but also for humane reasons, as it may reduce fear and anxiety ( 8 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…As well as these studies, there are also other studies comparing gabapentin's effects with other analgesic agents resulting in contradictory ideas. 15 It is known that the increased severity of surgery and magnitude of tissue injury are related with increases in the plasma levels of proinflammatory cytokines. 16 TNF-α and IL-6 are 2 early important features of acute injury that play a role in persistent postoperative pain syndromes.…”
mentioning
confidence: 99%